Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3748/wjg.v21.i33.9774
|View full text |Cite
|
Sign up to set email alerts
|

Bezoar-induced small bowel obstruction: Clinical characteristics and diagnostic value of multi-slice spiral computed tomography

Abstract: BI-SBO exhibits regional and seasonal characteristics. CT planar and contrast-enhanced scanning can be applied to diagnose and observe vascular conditions in obstructed zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…They concluded that CT scan was successful in identifying 100% of their patients with BI-SBO. Bezoars showed on the CT as ‘lumps with clear edges inside the intestinal cavity’ 6. They further discussed the use of contrast enhanced CT. Of their 35 patients, 18 underwent non-contrast abdomen and pelvis CT, and 17 had a contrast-enhanced examination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They concluded that CT scan was successful in identifying 100% of their patients with BI-SBO. Bezoars showed on the CT as ‘lumps with clear edges inside the intestinal cavity’ 6. They further discussed the use of contrast enhanced CT. Of their 35 patients, 18 underwent non-contrast abdomen and pelvis CT, and 17 had a contrast-enhanced examination.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 6 investigated the use of CT in diagnosing BI-SBO. They concluded that CT scan was successful in identifying 100% of their patients with BI-SBO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all these cases symptoms are similar and include abdominal pain, nausea and vomiting, inability to pass gas or bowel movements, and sometimes fever [1], so a correct differential diagnosis is important. Bezoars represent an infrequent cause of mechanical SBO and can occur in 0.4–4% of total cases, according to different authors [24].…”
Section: Introductionmentioning
confidence: 99%